Case report: Paralysis after epidural analgesia due to a hemorrhage of pure epidural venous hemangioma - Li, Jiahui; Xie, Pengyun; Liu, Xiaolei; Li, Daheng; Tang, Jing (Frontiers in Neurology, 2023)
Purpose To report a case of sudden paralysis after epidural analgesia to raise awareness of the condition and the importance of early identification and appropriate treatment of extradural venous angiomas. Clinical features A 28-year-old man with myofascial pain syndrome experienced paraplegia after receiving an epidural block for pain relief, which was later discovered to be caused by hemorrhage from extradural venous angiomas. Decompression surgery was performed immediately and successfully. A follow-up examination was performed 5 months after surgery. The patient reported improvement in urinary retention. The muscle strength in both his lower extremities had recovered to 4 out of 5 but still exhibited considerable residual spasticity. Conclusions Before administering epidural analgesia to relieve undetermined pain, it is prudent to carefully weigh potential benefits against potential risks to patient health to minimize the likelihood of complications.